GREEN MARKETING STRATEGY AS AN IMPLEMENTATION OF CONSUMER TRUST IN REALIZING SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Akbar, Shofif Sobaruddin; Puspitasari, Ratih Hesty (STIE Pelita Nusantara Semarang, 2025)
This study discusses the influence of green marketing strategies and Sustainable Development Goals (SDGs) on green purchasing behavior with trust as an intervening variable. The background of this study is based on global challenges related to climate change and the need for more sustainable consumption, especially in developing countries such as Indonesia. Although environmental awareness is increasing, green purchasing behavior is still low, so an effective marketing strategy is needed. The aim is to test the influence of green marketing strategies and SDGs on trust and green purchasing behavior, and to analyze the role of trust in mediating the relationship. This study focuses on consumers in East Semarang, using a quantitative approach with a survey method and data analysis using SmartPLS 3.0. The results of the study are expected to provide insight for companies in developing sustainable marketing strategies and increasing consumer trust in environmentally friendly products.